Pemaafan Dan Perilaku Agresi Siswa - Qarina, Sayyidati; Nashori, H. Fuad (Unisia, 2018)
This research is aimed to gain understanding of negative relation between forgiveness and aggression on high school student. The higher level of forgiveness resulting lower level of aggresiveness. The numbers of subject on this research is approximately 124 subjects. High school student both men and women are the criteria of the subjects. The scale which is used on this research is using forgiveness scale adapted from Nashori forginess scalematch with Nashory's aspects and aggresiveness aspect is modified based on Buss Perry Scale is course with Buss Perry. Corelation analysis is using Pearson methode with value at r= 0. 409 and p=0.000 (p < 0.001).That value indicate negative relationship between forgiveness and aggresiveness on high school student.